Pulmonary rehabilitation improves distance-saturation product in IPF: Greater benefits in patients with exercise-induced desaturation - Şahin, Hülya; Naz Gursan, Ilknur; Demirci Ucsular, Fatma; Karadeniz, Gulistan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: Exercise-induced dyspnea and desaturation are hallmark features of idiopathic pulmonary fibrosis (IPF) and are linked to disease severity and poor outcomes. The distance-saturation product (DSP), calculated by multiplying the walking distance by oxygen saturation, has been proposed as a mortality predictor. This study aimed to investigate the effects of a pulmonary rehabilitation (PR) program on clinical outcomes and DSP in two IPF patient groups: those with and without desaturation during the six-minute walk test (6MWT). Methods: IPF patients who completed a standardized PR program were included. Assessments before and after PR included spirometry, arterial blood gas analysis, Medical Research Council (MRC) dyspnea scale, 6MWT, St. George’s Respiratory Questionnaire (SGRQ), 36-Item Short Form Survey (SF-36), and Hospital Anxiety and Depression Scale (HADS). DSP was calculated at the end of the 6MWT. Patients with oxygen saturation ≤88% during baseline 6MWT were assigned to the desaturated group; others were assigned to the non-desaturated group. Results: Fifty patients were enrolled (20 desaturated, 30 non-desaturated). Following PR, only the desaturated group showed significant improvements in forced vital capacity (FVC), oxygen saturation, and SF-36 domains. In both groups, PaO₂, 6MWT distance, and DSP increased significantly, while MRC, SGRQ, and HADS scores decreased. However, the gains in 6MWT distance and DSP were significantly greater in the desaturated group. Conclusion: PR improved functional, psychological, and quality-of-life outcomes in both groups, with more pronounced benefits on sa in desaturated patients. Referral to PR is especially recommended for this subgroup.